Assessment of factors that affect financial sustainability of rural village community bank (VICOBA): A case of Nyamagana district - Ephraim, Charles (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirement for award of the Degree of Master of Science in Project Planning and Management (MSc. PPM) of Mzumbe University 2018